2019
DOI: 10.3390/nu11102359
|View full text |Cite
|
Sign up to set email alerts
|

Association between Different Animal Protein Sources and Liver Status in Obese Subjects with Non-Alcoholic Fatty Liver Disease: Fatty Liver in Obesity (FLiO) Study

Abstract: Non-alcoholic fatty liver disease (NAFLD) is considered the hepatic manifestation of metabolic syndrome. Obesity and unhealthy dietary habits are described as risk factors for NAFLD. The aim of this study was to investigate the association between the consumption of different animal protein sources and hepatic status in NAFLD adults. A total of 112 overweight/obese participants with NAFLD from Fatty Liver in Obesity (FLiO) study were evaluated at baseline. Diet, body composition, and biochemical variables were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Each item in the FFQ included a typical portion size and the frequencies of consumption were registered in nine categories that ranged from “Never or almost never” to “≥6 times/d”. The composition of the food items was derived from accepted Spanish food composition tables as previously described 17,28 . The adherence to the MedDiet was evaluated using a 17‐point screening questionnaire 29 .…”
Section: Methodsmentioning
confidence: 99%
“…Each item in the FFQ included a typical portion size and the frequencies of consumption were registered in nine categories that ranged from “Never or almost never” to “≥6 times/d”. The composition of the food items was derived from accepted Spanish food composition tables as previously described 17,28 . The adherence to the MedDiet was evaluated using a 17‐point screening questionnaire 29 .…”
Section: Methodsmentioning
confidence: 99%
“…Multiple environmental and genetic factors are involved in the onset and progression of NAFLD [6]. Concerning NAFLD treatments, weight loss induced by energy-restricted diets, physical activity promotion, and other lifestyle modifications have exhibited promising results leading to a better hepato-metabolic status [7,8]. Liver biopsy, the current reference standard, is an invasive and expensive procedure with some inherent surgical risks and only represents around 1/50,000 of the total hepatic volume [2,9]; however, it is still required for a definite diagnosis of NASH.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the composition of the diet may have an important role in the management of NAFLD [ 36 ], since the severity of NAFLD has been associated with an increase in oxidative stress and pro-inflammatory status [ 37 ]. Indeed, specific foods such as meat [ 38 ], fruits [ 39 ], glycemic index [ 40 ] or protein content [ 41 ] have been involved on pro-oxidative and antioxidant patterns in liver patients. Furthermore, lifestyle factors have been associated with NAFLD in a Mediterranean cohort [ 42 ], which have repeatedly reported that physical activity, exercise and sport practice are related to oxidative stress [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%